Compensation for Oil Pollution under Nigerian Law and the Problems of the Victims in Assessing the Damage - J. Adams Adoga-Ikong; Edidiong Jacob Udo; Patrick, C. Aloamaka; Edidiong Jacob Udo; Patrick C. Aloamaka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2021)
Since the discovery of oil in Nigeria, it has been woes due to the pollution of the environment caused by the exploration and exploitation of the products. This pollution has caused a lot of untold hardship on the people and the environment of the oil producing area of the country. This ranges from, sickness, such as common cold to very devastating and chronic diseases to the pollution of the farmlands, fish ponds, and general environmental degradation caused by the activities in the oil industry. Unfortunately, not much has been done by both the government and the oil companies to alleviate the sufferings of the people. Although there are laws put in place to address this ugly situation by way of compensation such as the Oil Pipelines Act, the Oil in Navigable Waters Act, Petroleum (Drilling and Production) Regulation among others. Also, there are common law principles such as, Nuisance, Trespass, Negligence etc. which are put in place as spring board for the redress of victims of oil pollution. The snag here is, how effective are these statutory and common laws principles in tackling this problem? Are the victims of oil pollution well compensated? Unfortunately, these laws have not done much hence, the victims are left either not compensated or not adequately compensated because of one technicality or other, which throws a burden on the plaintiff to prove his case. This work therefore, examined the various laws in place providing compensation to the victims of oil pollution and suggested that a strong enforcement of the laws will be a panacea for victims’ redress.